Amelia lost : the life and disappearance of Amelia Earhart - Fleming, Candace (Yearling, 2019)
Chronicles the dramatic search for pilot Amelia Earhart after she mysteriously disappeared during her attempt to circumnavigate the globe at its widest point. Includes black-and-white photos and traces her flight route.